THE EXTERNAL RECEPTION OF INTER-AMERICAN HUMAN RIGHTS LAW - Neuman, Gerald (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2011)
This article examines the ways in which Inter-American human rights law has been received and employed outside its own sphere. The Inter-American Court and Commission engage self-consciously in dialogue and borrowing from the global human rights system and the other regional human rights tribunals. Tracing the reciprocal influence of Inter-American developments is a complicated undertaking, because official texts may either understate or overstate the degree to which their authors have relied upon external sources. Examination of the jurisprudence of other human rights tribunals produces mixed results that require interpretation. The African and European regional tribunals have openly engaged with Inter-American precedents on procedure and substance from both the Court and the Commission, although less extensively than the Inter-American Court’s methodology leads it to draw from Europe. The International Court of Justice and the UN Human Rights Committee have generally avoided open reference to regional precedent in their institutional opinions, while arguably some tacit influences can be traced. Some express discussion of Inter-American precedent does occasionally appear in concurring or dissenting opinions. The Inter-American Court has had less success, however, in exporting its views on jus cogens.